Emphasizing the importance of digital storytelling in rural schools in Malaysia - Mohamed Rosli, Roziana (JARSSH, 2019)
Many teachers and students in rural schools ﬁnd that digital storytelling is difﬁcult to be implemented in the classrooms as compared to schools in the cities. This study explores how digital storytelling is accepted or rejected by teachers and students in Malaysian rural schools when it is introduced in the classroom. Digital storytelling according to Eisner (1998) allows students to share their stories outside of the traditional written form. Since communication terrain has changed dramatically over the last decade, digital story-telling is one way, which can be utilized to improve students’ communication ability. In tandem with the Malaysian government’s effort to introduce and maintain innovative teaching and learning in the classroom (Preliminary 2013-2025 Malaysia Education Report) this study focuses on the factors affecting students’ participation and communication delivery while involving in digital storytelling. It also provides ways in which teachers could engage students in classroom interaction to optimize students’ learning. This research will contribute to conceptualizing the ideas behind the perceptions of teachers and students towards digital literacy, especially in English language classrooms.